Visual brand identity (VBI) : Essential constituents in the construction of a brand’s visual look and the implementation of visual changes - Virtanen, Eveliina (fi=Turun yliopisto|en=University of Turku|, 2018)
Differentiating oneself from competition and breaking through the clutter of the modern, saturated marketplace has become increasingly complicated. In addition, consumers have become more powerful and critical towards formal marketing messages. These realities have led to a necessity for companies to turn more of their focus and resources toward the exploitation of visual communication. Visual brand identity (VBI) serves as a significant tool that helps brands to represent themselves and convey their essence. However, to date, proper conceptualisation of VBI has been limited and as a result, the purpose of this study is to provide a holistic and thorough examination of VBI. In addition, since the modern marketplace is characterised by constant change, brands are under pressure to renew their visual appearance on a regular basis in order to maintain relevancy. Therefore, a further aim of this study is to determine the procedures and strategies marketing experts employ in order to uphold an appropriate balance between the implementation of visual changes and the maintenance of a familiar VBI. The theoretical framework for the studied issues was predominantly formed by the concepts of brand identity, visual identity and visual brand identity. The most conventional visual brand elements were also closely examined, as were the notions of consistency, brand identification and brand familiarity. Potential reasons for, consequences of, and factors to be considered in the implementation of visual changes were also part of the theoretical framework. Finally, semi-structured theme interviews with eleven marketing experts were conducted. With the aspiration of contributing to the existing knowledge surrounding the topic, answers to the research questions were presented through the comparison and contrast of theory and the empirical findings. The findings revealed that VBI is a multidimensional construct that can serve as a valuable resource if understood and managed properly. Focus on the brand purpose is of utmost importance in the construction of VBI and rational reasoning is paramount to the decision-making process concerning a brand’s visual look. Through the two aforementioned factors, brands can become truly meaningful and consistent, which is crucial for the creation of brand recognition, brand familiarity and a system-like branding process. Furthermore, a major part of branding involves human-related factors that contribute to the success of VBI. In the implementation of visual changes, arbitrary or dramatic alterations should be avoided. Instead, changes should be subtle and form part of an ongoing brand evolution process.